RECENTLY DIAGNOSED SEVERE HIGH BLOOD PRESSURE IN A SUB-SAHARAN COUNTRY: EPIDEMIOLOGICAL, CLINICAL, THERAPEUTIC, EVALUATIVE ASPECTS AND FACTORS OF ADHERENCE TO THE TREATMENT. (June 2018) - Ouankou, C. Ngongang; Kapi, L.O. Chendjou; Kengne, A.P.; Blackett, K. Ngu; Kenfack, M. Azabji; Kaze, F.J.; Tsambang, W.L.; Ouankou, M.; Mfeukeu, L. Kuate
Abstract : Objective: Our objective was to determine the clinical presentations, evolution and factors of adherence to the treatment. We conducted nine months prospective cohort study, from January to September 2016 in Yaounde teaching Hospital. Design and method: We conducted nine months prospective cohort study, from January to September 2016 in Yaounde teaching Hospital. We recruited from members of the public who accepted voluntary blood pressure screening offered in various localities in Yaounde, and were aged 18 years or over. We examine them by doing assessment of target organs and evaluating the treatment and the adhesion to it. Results: Of a total of 6, 519 people who participated in the screening then 363 (5.6%) had severe HBP. Our cohort comprised 153 (42.1%) of these individuals with sustained severe hypertension, not on medication, who accepted the invitation to participate in the study. The range 45–54 years and 55–64 years were the most represented; the sex ratio was 0.9. The cardiovascular risk factors number range from 5 to 8 with a median of 6. Systolic BP ranged from 184 to 225 mmHg with a median of 200 mmHg; while the diastolic BP ranged between 111–132.5 mmHg with a median of 119 mmHg. Kidney injury (78.8%) was the main complication. We identified 3 clinical forms: hypertensive emergencies 121 (79.1%) cases and hypertensive crises 32 (20.9%) cases. The average rate of BP control over 6 months was 39%. The main cause of poor BP control was lack of therapeutic compliance. We registered one death at the 3rd month due to acute kidney injury. Conclusions: High blood pressure is remaining a major problem of public heath, not only because of the effects on the target organs, but mainly because of poor adherence to the treatment linked to poverty, and ignorance.